IMPLEMENTATION OF DISCUSSION METHODS AS A TOOL TO BALANCE CURRICULAR AND NON-CURRICULAR ACTIVITIES OF GRADE XI STUDENTS AT SMA NEGERI 17 JAKARTA BARAT - Septiniar Laoli; Nistari Waruwu; Septria Zega; Naharjo Tatubeket; Agusmawati Gulo (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2025)
Abstract This study aims to implement the discussion method as a tool to balance curricular and non-curricular activities for grade XI students at SMA Negeri 17 Jakarta Barat. The background of this study highlights the problem of imbalance between curricular and non-curricular activities, which results in a decline in academic achievement and a lack of active participation by students in learning. The research method used was Classroom Action Research (CAR) with the Kemmis and Taggart spiral model, carried out in two cycles covering planning, implementation, observation, and reflection. Data were collected through observation, interviews, tests, and student reflection. The findings show that the application of the discussion method increases active participation, critical thinking skills, and balance between academic and non-academic activities. Most students achieved learning completeness with a significant increase from cycle I to cycle II. In conclusion, the discussion method proved to be effective in creating more comprehensive learning and supporting the balanced character development of students. Recommendations were given to schools and teachers to optimize the application of this method as an innovative and participatory learning strategy. Keywords: Discussion method, Curricular activities, Non-curricular activities